Role of fine needle aspiration cytology in Metastatic lymphadenopathy - Nepal, Niraj (Journal of Nobel Medical College, 2016)
Background The most common site for metastases is lymph nodes for various types of cancers. It is a reliable and easy approachable as well as inexpensive method of diagnosis for the patient as well as for the pathologist. So, the recognition and establishing a preliminary diagnosis on patients presenting clinically with lymphadenopathy is of importance and especially categorizing whether it is an inflammatory lesion or metastatic or primary neoplastic lesion itself of the lymphnode.Material and Methods A prospective study in 1000 patients was performed of all presenting with cervical lymphadenopathies. This study was performed in the department of pathology, Nobel Medical College and Teaching hospital, Biratnagar, Nepal from the period of January 2013 to January 2016.Results Total number of cases included was 1000 of fine needle aspiration cytology in patients presenting with cervical lymphadenopathies. Out of the total 1000 cases 800 cases were benign lesions, 110 were malignant lesions, 70 cases were inflammatory lesions while 20 cases were inconclusive. Out of the 110 malignant cases, most common malignancy was squamous cell carcinoma, adenocarcinoma followed by ductal carcinoma of breast, small cell and non-small cell carcinoma, papillary carcinoma of thyroid and few cases of malignant melanoma and undifferentiated carcinoma.Journal of Nobel Medical College Vol.5(2) 2016; 26-31